mTOR signaling is activated by FLT3 kinase and promotes survival of FLT3- mutated acute myeloid leukemia cells - Weina Chen; Ηλίας Δράκος; Ioannis Grammatikakis; Ellen Schlette; Li Jiang; Vasiliki Leventaki; Efi Staikou-Drakopoulou; Efstratios Patsouris; Panayiotis Panayiotidis; L. Jeffrey Medeiros; George Z. Rassidakis (2010)
Abstract Activating mutations of the FLT3 gene mediate leukemogenesis, at least in part, through activation of PI3K/AKT. The mammalian target of rapamycin (mTOR)-Raptor signaling pathway is known to act downstream of AKT. Here we show that the mTOR effectors, 4EBP1, p70S6K and rpS6, are highly activated in cultured and primary FLT3 -mutated acute myeloid leukemia (AML) cells. Introduction of FLT3-ITD expressing constitutively activated FLT3 kinase further activates mTOR and its downstream effectors in BaF3 cells. We also found that mTOR signaling contributes to tumor cell survival, as demonstrated by pharmacologic inhibition of PI3K/AKT/mTOR, or total silencing of the mTOR gene. Furthermore, inhibition of FLT3 kinase results in downregulation of mTOR signaling associated with decreased survival of FLT3 -mutated AML cells. These findings suggest that mTOR signaling operates downstream of activated FLT3 kinase thus contributing to tumor cell survival, and may represent a promising therapeutic target for AML patients with mutated- FLT3 .